Effectiveness of Polyoxidonium in the treatment of chronic lower urinary tract infections in Women - Menon L. Caspian, Cove J. Gundel (Open Journal of Physicians and Surgeons, 2025)
Complicated and uncomplicated lower urinary tract infection (LUTI) in women is the leading reason for visiting a urologist. Debilitating dysuric symptoms of acute and chronic lower urinary tract infection significantly reduce the quality of life of these patients and very often cause dyspareunia and neurosis-like conditions. They often deprive women of a full night's sleep, normal working capacity during the day and their usual way of life in general. In some patients, chronic LUTI in the course of a long course is complicated by symptoms of incontinence, and ascending pyelonephritis and other complications leading to disability also occur. About 40% of women in the North Caucasus Federal District note at least one episode of acute LUTI - cystitis in their medical history. According to statistics, up to 35 million cases of acute LUTI are registered annually . Most often, they occur in women in the age groups of 18-38 years and 65 years and older. This is explained by the intensity of sexual life and the implementation of the reproductive function of patients in the first group and a decrease in the level of estrogens and, accordingly, the general and local immunity of patients in the second group.